Factors of Innate and Adaptive Local Immunity in Children with Primary Deficiencies of Antibody Formation - L.I. Chernyshova; S.A. Yakymovych; A.V. Chernyshov; B.V. Donskoy; L.V. Stamboli (Zaslavsky O.Yu., 2013)
In 40 children with various types of primary immunodeficiencies (PID) of antibody formation we examined factors of local immunity in saliva. It is found that in the saliva of children with PID of antibody formation in comparison with immunocompetent children the concentration of factors of adaptive immunity is significantly reduced. Lack of adaptive immunity in the PID of antibody formation to some extent is compensated by increased concentrations of innate immune factors on the mucous membranes - the free Sc, as well as lactoferrin in selective immunodeficiency of IgA. At PID of antibody formation we observed increased TNF-α level in the saliva, which may indicate the persistence of local inflammation on the membranes of the respiratory tract.